Training and Employment for Correctional Populations. (November 2021) - Duwe, Grant; Henry-Nickie, Makada
Education and employment are both moderate risk factors for recidivism. There is a well-documented relationship between low educational achievement and antisocial behaviors. Education programming in correctional facilities is crucial for improving the educational attainment of incarcerated and re-integrating populations. A brief discussion situates policy reform efforts against a backdrop of extensive research that has documented the interaction between employment and increased educational attainment as pivotal to reducing an individual's propensity to recidivate. The policies then focus on three pillars that reduce employment barriers for returning citizens: workforce training, educational upgrading, and regulatory employment barriers. In the short-term, policymakers should study and address systemic remedial educational needs in tandem with increasing access to and occupational skills-based training that builds a skill base congruent with the current labor market for incarcerated students. In the mid-term, it is essential to match policy support with the intersecting barriers faced by returning citizens. As an example of federal policies that can help center the public workforce development system around the need to improve quality employment outcomes for returning citizens, the DOL's dormant pilot Linking to Employment Activities Pre-Release (LEAP). Finally, policymakers should target other consequential screening barriers, such as the accuracy of criminal records that employers can check and have been shown to adversely affect employment prospects.